Development Of Supported Tio2 Photocatalyst Based Adsorbent For Photocatalytic Degradation Of Phenol. - Zainudin, Nor Fauziah; Abdullah, Ahmad Zuhairi; Mohamed, Abdul Rahman (2008)

(untitled)
The presence of harmful organic compounds such as phenols and their derivatives in water supplies and from industrial effluents is a topic of global concern. In recent years, it has received considerable attention as an alternative for treating industrial waste water.